Life history and phenology of Phylloicus pulchrus (Trichoptera: Calamoceratidae) in a tropical rainforest stream of Puerto Rico - Reyes-Torres, Limarie J. (2018)
Caddisflies are abundant, diverse, and important insects in freshwater ecosystems.  However our knowledge on their life history is incomplete, in particular for the Neotropics. The objectives of this study were to describe the life history and phenology of Phylloicus pulchrus in the Luquillo Experimental Forest, Puerto Rico. Eggs and larvae were reared to determine the species lifespan and time in each instar. Larval instars were determined based on a head width vs. pronotal suture length correlation (N= 120). Larvae and benthic leaf litter were sampled monthly at a headwater stream for a year; all specimens were classified into instars based on their case size. Adult P. pulchrus were sampled monthly for a year with a light trap and at various times with a Malaise trap. Monthly environmental variables were related to species and sex abundance. There was a gradient of egg development where eggs (within compound masses) closest to the water were more developed. There were five larval instars and reared larvae showed longer development times and more variable body measurements in later instars. The best correlation for larval instar determination was case length-head width (Pearson= 0.90, P= 2.2e-16, N= 120). Phylloicus pulchrus has a multivoltine life cycle, with asynchronous larval development. Adult abundance was low. First to third instar larvae were influenced significantly by rainfall and rainfall seasonality had a negative significant effect on second instar larval abundance (ANOVA= 7.45, P= 0.02).Compound egg masses were probably oviposited by different females that gathered for oviposition. Phylloicus pulchrus follows the predominant developmental characteristic of Trichoptera of having five larval stages. Development times were longer than expected (longest times for a Phylloicus species) and may be an effect of laboratory rearing. The influence of rainfall (and seasonality) on different larval instars highlights the importance of this variable on early larval development. The cause of low adult abundance remains unclear, but may be related to low emergence rates and trap efficiency. Rev. Biol. Trop. 66(2): 814-825. Epub 2018 June 01.